The relationship between interaural delay in binaural gap detection and sensitivity to temporal fine structure in young adults with or without musical training experience - Ding, Yu; Lei, Ming; Cao, Chunmei (Frontiers in Neuroscience, 2022)
Humans can detect the presence of a break in interaural correlation (BIC, also called binaural gap) even if a large interaural time delay (ITD) is introduced, which is important for detecting, recognizing, and localizing sounds in everyday environments. To investigate the relationship between interaural delay on binaural gap detection and the sensitivity of temporal fine structure (TFS), 40 young college students with normal hearing took the BIC delay threshold test, TFS1 test (test of monaural TFS sensitivity), and TFS-AF test (test of binaural TFS sensitivity). All participants were asked whether they had any musical training experience in their childhood. Results showed that the BIC delay threshold was significantly correlated with the TFS1 test (r = -0.426, p = 0.006), but not with the TFS-AF performance (r = -0.005, p = 0.997). The correlation between BIC delay threshold and monaural TFS sensitivity was observed in the non-music training group, (r = -0.508, p = 0.010) but not the music training group (r = -0.290, p = 0.295). These findings suggest that the interaural delay on binaural gap detection is related to the monaural sensitivity of TFS, this significant correlation was mainly found in young adults without musical training experience.